Isotopic Evaluation of the Nutritional Contribution of Poultry By-product Meal and Fish Meal to the Growth of Pacific White Shrimp, Litopenaeus vannamei - Gamboa Delgado, Julián; Castañeda Solís, Juan de Dios; Nieto López, Martha Guadalupe; Villarreal Cavazos, David Alonso; Cruz Suárez, Lucía Elizabeth (Wiley, 2014)
The nutritional contribution of the dietary nitrogen supplied by poultry by-product meal (PBM) and fish meal (FM) to the somatic growth of Pacific white shrimp, Litopenaeus vannamei was assessed by means of stable isotope analysis. Seven experimental diets were formulated with different proportions of PBM replacing FM. Mixed diets were formulated to replace 0, 35, 50, 65, 80, 95 and 100 % of FM with PBM, on a dietary nitrogen basis. At the end of the experiment, there were no significant differences in survival among dietary treatments (89±5 %); however, significant differences in final wet weights were observed. Diets having FM replacement levels of 35 and 50% with PBM, promoted mean final weights (708-789 mg) similar to those observed in shrimps fed on diet containing 100% FM (874 mg). Shrimp final mean weight significantly decreased as a function of PBM inclusion (r= -0.98) due to the use of only two dietary nitrogen sources and by possible nutritional restrictions as PBM levels increased. The relative proportions of dietary nitrogen supplied by PBM and FM were incorporated in muscle tissue at proportions that were statistically similar to those established in the dietary formulations.